Dean of the School of Lifelong Learning - Office of the Chancellor - De La Salle University, Manila (Animo Repository, 2021)
After a process of consultation, Br Bernie Oca pleased to announce the appointment of Dr. Rodiel C. Ferrer as Dean of the School of Lifelong Learning effective 1 October 2021.